上古汉语的定语反身以及 中古汉语的“自己”的产生 = Adnominal reflexive pronoun in archaic Chinese and the origin of “ziji” - 钟惠芬 Chong, Wai Fun (2012)
程工（1999）提出“自己”是上古汉语反身代词“自”与代名词“己”结合而成的复合词。朱冠明（2007）认同其说法，并揭示“自己”在定语位置成词。由于上古的“自”并没有定语用法，因此他推测“自”在中古时受到佛经影响而产生了定语用法。然而，我们发现“自己”初成词时绝大多数呈局部约束表现，不符合我们预料中的局部约束和长距离约束参半，故我们认为朱氏的解释尚有未完善之处。另外，我们认为中古“自”的定语用法除了受到语言接触影响，亦有可能是由语言内在的因素所造成的。故本文尝试回到上古时期探讨其他有可能致使“自”定语用法产生的来源。通过考察《左传》里的“V其NP”，本文发现“其”在上古时期具有定语反身功能，但这功能会因为搭配不同的动词而显现或被抑制。因此，我们将“其”看作是上古汉语不典型的定语反身代词。Chen, (程工1999) proved that “ziji”(自己), the so-called “monomorphemic reflexive” by many, is in fact a compound of a reflexive(“zi”自) and a generic pronoun(“ji”己) from Archaic Chinese. However, the explanation on how the two morphemes are combined was not given Zhu, (朱冠明2007) reckoned that “zi”(自) developed a new usage as a possessive since the East Han Dynasty through language contact. He believed that the possessive usage was transferred by the translators of Chinese Buddhist scriptures. Thus the two words “zi”(自) and “ji”(己) could co-occur in the adnominal possessive position and induced the combination of the two. In this paper, we are going to propose another possibility that possessive usage of “zi”(自) might have come from. Besides, we observed that when “ziji” was newly formed in East Han Dynasty, it seemed to take a local antecedent instead of showing long distance binding, which differs from Modern Chinese “ziji”. After examining the function of “qi”(其) in the construction of “V+qi(其)+NP” in Zhuo Zhuan(《左传》), we found that “qi”(其) possesses adnominal possessive usage and can be reflexive sometimes when it matches the specific verbs in Archaic Chinese. However, when it matches with some other verbs, its reflexive function would be disabled. Thus “qi”(其) can yet to be a adnominal possessive reflexive pronouns in Archaic Chinese.